Lumbar Radiofrequency Rhizotomy in Patients with Chronic Low Back Pain Increases the Diagnosis of Sacroiliac Joint Dysfunction in Subsequent Follow-Up Visits - Varun Kumar Rimmalapudi; Sanjeev Kumar (Pain Research and Management, 2017)
Chronic back pain is often a result of coexisting pathologies; secondary causes of pain can become more apparent sources of pain once the primary pathology has been addressed. The objective of our study was to determine if there is an increase in diagnosis of Sacroiliac joint pain following a Lumbar Rhizotomy. A list of patients who underwent Lumbar Radiofrequency during a 6-month period in our clinic was generated. Records from subsequent clinic visits were reviewed to determine if a new diagnosis of SI joint pathology was made. In patients who underwent a recent Lumbar Rhizotomy procedure to treat facetogenic pain, the prevalence of Sacroiliac joint pain increased to 70%. We infer that there is a significant increase in the diagnosis of Sacroiliac joint syndrome following a Lumbar Rhizotomy, potentially due to unmasking of a preexisting condition. In patients presenting with persistent back pain after Lumbar Rhizotomy, the clinician must have a high degree of suspicion for latent Sacroiliac joint pain prior to attributing the pain to block failure. It would be prudent to use >80% relief of pain after a diagnostic medial branch block as a diagnostic criterion for facetogenic pain rather than the currently accepted >50% in order to minimize unmasking of preexisting subclinical pain from the SI joint.